Analysing Risk Preferences and Time Preferences with respect to Smoking Status and Smoking Intensity - Preston, Charles (School of Economics, 2020)
Smoking is a leading cause of death worldwide, and thus the behavioural components need to be understood to mitigate the damage caused by the practice. The relationship between smoking and factors such as risk preferences and time preferences has been the subject of a growing body of literature. This paper evaluates experimental data from smokers and nonsmokers at the University of Cape Town collected in 2016 and 2017. Maximum likelihood estimation is used to estimate models of risk preferences and time preferences. The results highlight that smokers are less risk averse than non-smokers; that smokers discount more heavily than non-smokers; that greater smoking intensity is correlated with lower risk aversion; and that greater smoking intensity is not related to discounting behaviour. In some specifications the relationship between smoking intensity and risk aversion is parabolic, and as such moderate smokers are less risk averse than heavy smokers and light smokers. In conclusion, smokers tend to discount more heavily than non-smokers, and lower smoking intensity is associated with greater risk aversion than higher smoking intensity.